Compensating justice beats leaky buckets: an experimental investigation - Eva Camacho Cuena; Tibor Neugebauer; Christian Seidl (Kiel University, Department of Economics, 2005)
Leaky-bucket transactions can be regarded as income transfers allowing for transaction costs. In its most rudimentary form, leaky-bucket transactions trace out the maximum "leakage" of transaction costs before income inequality is exacerbated, or before a welfare loss is experienced. This notion suggests that part of the income transfer should reach the transferee in order to keep the degree of income inequality or social welfare intact. However, in general, this conjecture is theoretically wrong. Rather there exists a unique benchmark such that it holds only for transfers among income recipients below the benchmark. When both are above the benchmark, the transferee has to be given more than the amount taken from the transferor, and when they are on opposite sides of the benchmark, both should experience an income loss. These three cases cover progressive transfers only. Three more cases apply to regressive transfers, and six more cases apply to income gains. Each of these twelve cases is covered by the present paper. Yet experimental research for three families of renowned income inequality measures and their associated social welfare functions shows poor empirical evidence. Subjects' perceptions to maintain the degree of income inequality rather follow a simple precept: If someone gains income, the other person involved should be positively compensated, and if someone loses income, the other person involved should be negatively compensated. This expresses sort of compensating justice rather than restoration of the former degree of income inequality, or of the former level of social welfare. It requires different axioms of inequality measurement to comply with subjects' perceptions.
Keywords: D63; D31; C91; 330; Einkommensverteilung; Disparitätsmass; Gerechtigkeit; Spieltheorie; Experiment; Soziale Wohlfahrtsfunktion; Theorie